ASSESSING THE EFFECTIVENESS OF WORK-FROM-HOME IMPLEMENTATION AND PERFORMANCE MONITORING IN THE DIGITAL WORKPLACE: A DIGITAL HRM PERSPECTIVE - Defi Efisa; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (PT. Hasba Edukasi Mandiri, 2026)
The widespread adoption of Work-from-Home (WFH) practices has transformed the way organizations manage employee performance in the digital workplace. Supported by Digital Human Resource Management (Digital HRM), organizations increasingly rely on digital technologies to facilitate communication, monitor employee performance, and maintain productivity while ensuring workforce flexibility. This study aims to assess the effectiveness of Work-from-Home implementation and performance monitoring from a Digital HRM perspective. This study employs a qualitative literature review approach by analyzing recent journal articles published between 2021 and 2026. The literature was collected from reputable databases, including Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, and Taylor & Francis. The selected studies were analyzed using thematic analysis to identify key trends, challenges, and best practices in managing remote work and digital employee performance. The findings indicate that effective Work-from-Home implementation enhances employee flexibility, work-life balance, and organizational productivity when supported by digital collaboration platforms and performance monitoring systems. Digital HRM enables organizations to improve communication, evaluate employee performance using objective indicators, and support data-driven decision-making. However, challenges related to employee engagement, digital competencies, cybersecurity, and performance evaluation remain important considerations for organizations. The study concludes that Digital HRM plays a significant role in optimizing Work-from-Home implementation and strengthening organizational performance in the digital workplace. The findings provide practical insights for organizations seeking to develop effective remote work strategies while maintaining employee productivity and long-term organizational sustainability.